European Trust Crisis? - Gunther Tichy (Wirtschaftsdienst)
Abstract Europe is said to be in a trust crisis. The finance crisis and the euro crisis caused a wide-ranging and sustained loss of trust and the media suspected this to be the culmination of a long-term trend. This may be true for the United States but not for Europe. Trust in Europe recovered within a decade, but with significant regional differences. While trust in democracy is not at all endangered in the EU’s northern and central countries, it could be at risk in the southern and the eastern ones. The paper shows that the problems in the East are exaggerated and may turn out as transitory, while the political instability in the South is more risky. Due to the fact that almost all member countries manifest a relatively high trust in the EU and a strong resolve to remain, these problems are unlikely to put European democracy at risk.